2017
DOI: 10.1038/s41598-017-18352-4
|View full text |Cite
|
Sign up to set email alerts
|

Alternative dominance of the parental genomes in hybrid cells generated through the fusion of mouse embryonic stem cells with fibroblasts

Abstract: For the first time, two types of hybrid cells with embryonic stem (ES) cell-like and fibroblast-like phenotypes were produced through the fusion of mouse ES cells with fibroblasts. Transcriptome analysis of 2,848 genes differentially expressed in the parental cells demonstrated that 34–43% of these genes are expressed in hybrid cells, consistent with their phenotypes; 25–29% of these genes display intermediate levels of expression, and 12–16% of these genes maintained expression at the parental cell level, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In our previous study, we evaluated the expression of Tubb3 in undifferentiated E14Tg2aSc4TP6.3 ES cells. 10 Actually, in our experiment, Tubb3 was detectable in undifferentiated ES cells, and its expression level was only 10 times lower than that of such pluripotency markers as Sox2 and Nanog. It is still unclear, whether this Tubb3 expression is the result of a partial differentiation or normal for undifferentiated ES cells.…”
Section: Discussionmentioning
confidence: 49%
“…In our previous study, we evaluated the expression of Tubb3 in undifferentiated E14Tg2aSc4TP6.3 ES cells. 10 Actually, in our experiment, Tubb3 was detectable in undifferentiated ES cells, and its expression level was only 10 times lower than that of such pluripotency markers as Sox2 and Nanog. It is still unclear, whether this Tubb3 expression is the result of a partial differentiation or normal for undifferentiated ES cells.…”
Section: Discussionmentioning
confidence: 49%
“…The second explanation is corroborated by the known fact that partially differentiated cells are always present among ES cells. In our previous study we evaluated expression of Tubb3 in undifferentiated E14Tg2aSc4TP6.3 ES cells (Matveeva et al 2017). Actually, in our experiment, Tubb3 was detectable in undifferentiated ES cells, and its expression level was only ten times lower than that of such pluripotency markers as Sox2 and Nanog.…”
Section: Egfp Expression In Undifferentiated Dges1-tubbegfp Es Cells mentioning
confidence: 70%
“…Cytogenetic analysis for ES cell lines was carried out during passages 6-10. Preparation of metaphase chromosomes from the cells was performed as previously described (Matveeva, Fishman, Zakharova, Shevchenko, Pristyazhnyuk, Menzorov and Serov, 2017). Metaphase plates were analyzed using a Carl Zeiss Axioplan 2 imaging microscope (Jena, Germany) with CoolCube1 CCD-camera and processed using the ISIS (In Situ Imaging System, MetaSystems GmbH, Altlussheim, Germany) software in the Public Center for Microscopy SB RAS, Novosibirsk.…”
Section: Es Cell Cytogenetic Analysismentioning
confidence: 99%
“…At the same time, it was shown that primary mouse carcinoma cells and malignant melanoma cell line remain amenable to reprogramming to iPSCs [ 10 , 29 , 30 ]. Also it was shown that immortalized mouse fibroblast cells m5S can be efficiently reprogrammed via cell fusion with ESCs [ 44 ]. The two situations, however, cannot be compared one-to-one, because mechanism of cell fusion-based reprogramming might be significantly different from reprogramming driven by OKSM [ 21 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also it was shown that immortalized mouse fibroblast cells m5S can be efficiently reprogrammed via cell fusion with ESCs [ 44 ]. The two situations, however, cannot be compared one-to-one, because mechanism of cell fusion-based reprogramming might be significantly different from reprogramming driven by OKSM [ 21 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%